Assessment of activity energy expenditure during competitive golf: The effects of bag carrying, electric or manual trolleys - Kasper, A. M.; O`Donnell, A.; Langan-Evans, C.; Jones, A.; Lindsay, A.; Murray, A.; Close, G. L. (European Journal of Sport Science, 2023)
Golf is a sport played around the globe, with an estimated 42.6 million people playing within the United Kingdom and United States of America alone. To date there is limited data on the energy expenditure of golf. The present study assessed the activity energy expenditure (AEE) of 16 high-standard (handicap under 5) golfers who completed 3 rounds of competitive golf either carrying the golf bag (BC), using a manual push trolley (MT) or an electric trolley (ET) (Stewart Golf, Gloucester, UK). Prior to each round, participants were fitted with an Actiheart® accelerometer (Camntech, Fenstanton, UK) to estimate AEE, whilst ratings of perceived exertion (RPE) and enjoyment were collected following each round. Data were analysed using a one-way repeated measures ANOVA, with Hedges g effect sizes (ES) calculated. Mean (SD) AEE was 688 ± 213 kcal for BC, 756 ± 210 kcal for MT and 663 ± 218 kcal for ET (p=0.05) although these differences were deemed small or less. The ET condition resulted in the lowest mean heart rate, moderate or very large from BC or MT respectively. There were no significant differences in enjoyment although perceived exertion was lowest in the ET condition. In summary, we report meaningful differences in AEE between the 3 conditions (p=0.05), with perceived exertion and maximum HR were lowest when using the electric trolley. Golf may be considered as an effective intervention to increase step count and improve physical activity levels across the general population regardless of transportation methods of clubs.